A guide for the company Norðurál : inventory management and quality improvements in a warehouse - Helga Kristinsdóttir 1992- (2019)
Verkefnið er lokað eins og er að beiðni Norðuráls. This project is a guide for the company Norðurál, that contains a description of how it is possible to improve inventory management and do quality improvements of processes in a warehouse. Norðurál on Grundartangi in Iceland, is a company that produces aluminum. One of Norðurál´s warehouses is examined in this project. The warehouse contains safety equipment, consumables and spare parts. The project includes two examples. In the first one, the Economic order quantity (EOQ) formula is used for few products in the warehouse. The example includes a simulation, to see if there is potential for savings and improvements of the inventory management, by using the EOQ formula. The second one, is an example of using Kume ́s 7 steps for one particular process in the warehouse, to see how it is possible to do quality improvements. In the end, there is discussion about possible automation in the warehouse and the inventory management. Þetta verkefni er leiðarvísir fyrir fyrirtækið Norðurál. Verkefnið inniheldur lýsingu á því hvernig mögulegt er að bæta birgðasýringu og gera gæðaumbætur á ferlum í vöruhúsi. Norðurál á Grundartanga, er fyrirtæki sem framleiðir ál. Eitt af vöruhúsum Norðuráls er skoðað í þessu verkefni. Vöruhúsið inniheldur öryggisbúnað, rekstrarvörur og varahluti. Verkefnið inniheldur tvö sýnidæmi. Í fyrsta dæminu er Economic order quantity (EOQ) formúlan notuð á nokkrar vörur í vöruhúsinu. Í dæminu er gerð hermun til þess að sjá hvort það sé möguleiki á sparnaði og umbótum á birgðastýringunni, með því að nota EOQ formúluna. Í seinna dæminu er 7 þrepa ferli Kumes notað á einn ákveðinn feril í vöruhúsinu, til þess að sýna hvernig hægt sé að fara í gegnum gæða umbætur. Í lokin eru umræður á mögulegri sjálfvirkni á birgðastýringunni og í vöruhúsinu. Verkefnið er lokað eins og er að beiðni Norðuráls.